Asset prices, exchange rates and the current account - Marcel Fratzscher; Luciana Juvenal; Lucio Sarno (European Central Bank (ECB), 2007)
This paper analyses the role of asset prices in comparison to other factors, in particular exchange rates, as a driver of the US trade balance. It employs a Bayesian structural VAR model that requires imposing only a minimum of economically meaningful sign restrictions. We find that equity market shocks and housing price shocks have been major determinants of the US current account in the past, accounting for up to 32% of the movements of the US trade balance at a horizon of 20 quarters. By contrast, shocks to the real exchange rate have been much less relevant, explaining less than 7% and exerting a more temporary effect on the US trade balance. Our findings suggest that sizeable exchange rate movements may not necessarily be a key element of an adjustment of today's large current account imbalances, and that in particular relative global asset price changes could be a more potent source of adjustment.
Keywords: F32; F40; C30; 330; Bayesian VAR; current account; Exchange Rates; global imbalances; sign restrictions; Leistungsbilanz; Wechselkurs; Börsenkurs; Immobilienpreis; USA; G7-Staaten